Different mechanisms of Ca2+ regulation that influence synaptic transmission: comparison between crayfish and Drosophila neuromuscular junctions. - Desai-Shah, M.; Cooper, R.L. (Synapse (New York, N.Y.), 2009)
A brief historical background on synaptic transmission in relation to Ca(2+) dynamics and short-term facilitation is described. This study focuses on the mechanisms responsible for the regulation of intracellular calcium concentration ([Ca(2+)](i)) in high output terminals of larval Drosophila compared to a low-output terminal of the crayfish neuromuscular junction (NMJ). Three processes; plasmalemmal Na(+)/Ca(2+) exchanger [NCX], Ca(2+)-ATPase (PMCA), and sarcoplasmic/endoplasmic Ca(2+)-ATPase (SERCA) are important in regulating the [Ca(2+)](i) are examined. When the NCX is compromised by reduced [Na(+)](o), no consistent effect occurred; but a NCX blocker KB-R7943 decreased the excitatory postsynaptic potential (EPSP) amplitudes. Compromising the PMCA with pH 8.8 resulted in an increase in EPSP amplitude but treatment with a PMCA specific inhibitor carboxyeosin produced opposite results. Thapsigargin exposure to block the SERCA generally decreases EPSP amplitude. Compromising the activity of the above Ca(2+) regulating proteins had no substantial effects on short-term depression. The Kum(170TS) strain (with dysfunctional SERCA), showed a decrease in EPSP amplitudes including the first EPSP within the train. Synaptic transmission is altered by reducing the function of the above three [Ca(2+)](i) regulators; but they are not consistent among different species as expected. Results in crayfish NMJ were more consistent with expected results as compared to the Drosophila NMJ. It is predicated that different mechanisms are used for regulating the [Ca(2+)](i) in high and low output synaptic terminals.